Sperm Protein17 is an Oncofetal Antigen: A Lesson From a Murine Model. (3rd September 2014) - Arnaboldi, F.; Menon, A.; Menegola, E.; Renzo, F. Di; Mirandola, L.; Grizzi, F.; Figueroa, J. A.; Cobos, E.; Jenkins, M.; Barajon, I.; Chiriva-Internati, Maurizio
<x xml:space="preserve">Abstract</x> Sperm protein 17 (Sp17) was originally identified in the flagellum of spermatozoa and subsequently included in the subfamily of tumor-associated antigens known as cancer-testes antigens (CTA). Sp17 has been associated with the motility and migratory capacity in tumor cells, representing a link between gene expression patterns in germinal and tumor cells of different histological origins. Here we review the relevance of Sp17 expression in the mouse embryo and cancerous tissues, and present additional data demonstrating Sp17 complex expression pattern in this murine model. The expression of Sp17 in embryonic as well as adult neoplastic cells, but not normal tissues, suggests this protein should be considered an "oncofetal antigen." Further investigations are necessary to elucidate the mechanisms and functional significance of Sp17 aberrant expression in human adult cells and its implication in the pathobiology of cancer.